How do doctors decide whether it is appropriate to treat people with VTE and advanced cancer?. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Sheard, Laura; Dowding, Dawn; Johnson, Miriam; Prout, Hayley; Noble, Simon; Maraveyas, Anthony
Abstract : Background: Studies have shown that long-term LMWH (low molecular weight heparin) is superior to warfarin for ambulant, good performance status cancer patients with venous thromboembolism (VTE) and is standard care. Patients with poor performance status are largely excluded from these studies. We explored the barriers for doctors in their investigation and treatment of advanced cancer patients with VTE. Method: Qualitative in depth interview study conducted with 45 participants (oncologists, palliative medicine doctors and GPs) working across a range of grades in Yorkshire, England and South Wales. Results: A strong theme emerged from the data about whether doctors considered it ethically appropriate to investigate and/or treat a patient with advanced cancer for VTE. The expected prognosis of the patient was a pivotal factor in decision making. Doctors were more willing to investigate and treat if the patient had a better prognosis. There was considerable debate whether LMWH should be used in patients likely to die within days/weeks and whether these patients should be moved for investigation, with concerns about inflexible ambulance transport and worries that hospital was not able to manage such unwell patients. Uncertainty existed about when LMWH injections should cease with some feeling a sense of over-caution in their own and others' treatment of patients as a result. Participants diverged on whether dying of a PE was 'a good way to go' with a minority viewing LMWH treatment as 'overmedicalisation'. The lack of evidence base in this patient group was observed. Illustrative quotations will be employed. Conclusion: The personal ethical framework of doctors plays a large role in medical decisions. Acknowledging this via empirical research informs a scant evidence base about how decisions are made for VTE management.